Improving Critical Thinking Skill of Students using aRPiGDs:An Effective and Alternative Method to Role Play - Dol, Sunita M.; Halkude, S. A. (Journal of Engineering Education Transformations, 2018)
Using various active learning strategies namely Think-Pair-Share, Peer-Instruction, Debate, Jigsaw, Problem based Learning, Game based Learning, Project based Learning, Team-Pair-Solo, etc, we engage the students in learning process. Role play is an activity where students perform the real time case study, to express the concept. Looking to efforts required, it is recommended to opt for the animated role play through effective video for demonstration. In the present study, we considered the newly designed activity using Animated Role Play Immediate Group Discussion followed by Sharing in the classroom (aRPiGDs). In this activity, instructor creates animated role play video and plays that video in the class. Entire class is further divided into a group of 7-8 students for studying role play and to identify the pro and cons of various methods. After discussion, each group shares their findings in the form of pros and cons on the topic. This activity is experimented for the course Operating System of Third Year Computer Science and Engineering. Feedback from the students at the end of the activity is taken to assess their learning through aRPiGDs.